Incisional surgical site infections in obstetric and gynecological procedures in a tertiary care hospital in Northern India - Chandra, Savita; Saxena, Shodashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: To find the incidence of incisional surgical site infection (ISSI) in obstetric and gynecological procedures, the risk factors, the microbial spectrum, the antibiotic sensitivity and the impact on the hospital stay. Methods: A prospective observational study was done under the department of obstetrics and gynecology, Era’s Lucknow medical college and hospital. All consecutive patients who underwent caesarean section, vaginal delivery with episiotomy, laparotomy, and hysterectomy were included in this study. Laparoscopic surgeries were excluded. Results; In this series of 646 surgeries, 6.18% developed ISSI. In the category of major surgeries, the ISSI rate was 8.89%. Amongst the 185 episiotomies 1.6% gaped. Anemia, diabetes mellitus, excess body weight, emergency or elective surgery, rapid built up of hemoglobin with blood transfusion, previous caesarean scar and tobacco intake were the risk factors identified. Coagulase negative staphylococcus was the dominant microbe. Antibiotic sensitivity to linezolid was found in 50% of the ISSI cases followed by amikacin, clindamycin and some others. The mean hospital stay was 13 days while the maximum was 26 days. Conclusions: The study established the current status of incisional surgical site infections, identified the risk factors, the microbial spectrum, the antibiotic sensitivity and the need for further studies using a preventive approach.